Plectin–intermediate filament partnership in skin, skeletal muscle, and peripheral nerve - Castañón, Maria J. (Springer Berlin Heidelberg, 2013)
Plectin is a large, 500-kDa, intermediate filament (IF)-associated protein. It acts as a cytoskeletal crosslinker and signaling scaffold, affecting mechanical as well as dynamic properties of the cytoskeleton. As a member of the plakin family of cytolinker proteins, plectin has a multidomain structure that is responsible for its vast binding portfolio. It not only binds to all types of IFs, actin filaments and microtubules, but also to transmembrane receptors, proteins of the subplasma membrane protein skeleton, components of the nuclear envelope, and several kinases with known roles in migration, proliferation, and energy metabolism of cells. Due to alternative splicing, plectin is expressed as various isoforms with differing N-terminal heads that dictate their differential subcellular targeting. Through specific interactions with other proteins at their target sites and their ability to bind to all types of IFs, plectin molecules provide strategically located IF anchorage sites within the cytoplasm of cells. In this review, we will present an overview of the structural features and functional properties of plectin and discuss recent progress in defining the role of its isoforms in stress-prone tissues and the implicated diseases, with focus on skin, skeletal muscle, and Schwann cells of peripheral nerve.